PENGARUH KOMUNIKASI, LINGKUNGAN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT ASIA RECYCLE MANDIRI - Kumalasari, Galuh Niken; Cahyani, Rusnandari Retno; Mutiasari, Annisa Indah (Universitas Malahayati, 2024)
This study aims to examine and analyze the influence of communication, work environment, and motivation on employee performance. The subjects of this study are contract employees at PT Asia Recycle Mandiri. The sample used consisted of 160 respondents. The analysis method applied is descriptive quantitative using multiple linear regression analysis techniques.Partial test results indicate that the communication variable does not significantly affect employee performance, with a t-value of 0.471 and a significance level of 0.638. Since t-value < t-table (0.471 < 1.97490) and the significance level > 0.05 (0.638 > 0.05), H1 is rejected and H0 is accepted.In contrast, the work environment variable shows a significant influence on employee performance, with a t-value of 6.080 and a significance level of 0.000. Since t-value > t-table (6.080 > 1.97490) and the significance level < 0.05 (0.000 < 0.05), H2 is accepted and H0 is rejected.The motivation variable also significantly influences employee performance, with a t-value of 3.084 and a significance level of 0.002. Since t-value > t-table (3.084 > 1.97490) and the significance level < 0.05 (0.002 < 0.05), H3 is accepted and H0 is rejected.Thus, the work environment and motivation variables are proven to have a significant influence on the performance of employees at PT Asia Recycle Mandiri, while communication does not have a significant influence.